CARREIRAS GERENCIAIS: UM ESTUDO EXPLORATÓRIO - Paula, Vilson Vieira de (2012)
THE business world studied by managerial literatures spends little efforts on building knowledge for the work of the professional Executive; despite of they have a direct connection with the most important paths adopted by the organization. Executives must have specific characteristics to perform this function, which besides of well remunerated, is imbued with responsibilities and frequent challenges. This research aims to analyze aspects of the daily life and career of professionals who work in the stratum of executive of a company, addressing also the models of careers that are part of the leverage processes in the life of these professionals. In order to achieve these goals, there have been made field researches, both qualitative and quantitative, in with 14 male and female executives were interviewed, and surveys applied to 126 individuals of this same strata, working at a variety of sectors, of Rio de Janeiro in 2012.